African Food Security Fellows’ Perceptions of Their Experiences in the United States: Reflective Journaling as a Way to Interpret and Understand an International Experience - Denise George; M. Craig Edwards; Shelly Sitton; D Dwane Cartmell II; Cindy Blackwell; J. Tanner Robertson (Journal of International Agricultural and Extension Education, 2014)
The study reports on a reciprocal exchange program funded by the U.S. Department of State. It involved 14 Food Security Fellows, including seven each from Kenya and Uganda, who were community leaders, policymakers, and media professionals. The Fellows experienced afive-week training program on issues of food securityand the unique role improved communication networks could play in reducing food insufficiency in their countries. During their exchange, the Fellows were asked to keep reflective journals chronicling their training experiences and interactions with Americans and their culture. The journal entries were transcribedandcoded, and emergent themeswere identified in concert with the study’s purpose and research questions. Established procedures to address researcher reflexivity and enabletransferability of the findings were followed. The data analysis yielded 41 codes from which 11 themeswere derived. The Fellows expressed a more positive attitude about Americans and the United States at the program’s end. They also described an appreciation for the role of youth development in agriculture and the need for extension educators,researchers, and university personnelto work together to ensure a nation’s food security. Future exchanges should provide participants with an internship experience instead of only job shadowing opportunities
Keywords: Africa; food security; international experiences; reflective journaling